Perkembangan Moral Menurut Lawrence Kohlberg dan Perkembangan Empati Menurut Martin L. Hoffman: Integrasi Nilai dan Perasaan dalam Pembentukan Moralitas Perempuan - Lidiya Yati Sofiana; Lilita Efquany; Ersa Nur Khasanah; Naisyla Rahmadiah; Azriel Restu Fajar; Sugeng Sejati (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
The formation of women’s morality is a complex process involving the interaction between cognitive and affective dimensions in human psychological development. Lawrence Kohlberg’s theory emphasizes that morality develops through logical stages of reasoning oriented toward universal principles of justice, while Martin L. Hoffman highlights empathy as the affective foundation driving moral behavior. This study aims to integrate these two theories to provide a comprehensive understanding of women’s moral formation through a qualitative-analytical library research approach. The analysis examines the assumptions, strengths, and limitations of each theory to identify the convergence between cognitive morality and affective empathy. The findings reveal that justice and care are complementary aspects of human morality. Empathy serves as the emotional engine motivating moral actions, whereas cognitive reasoning provides direction and justification. Mature women’s morality is not solely based on care or empathy but represents a dynamic synthesis between rational thought and emotional understanding. This integration reflects a more holistic and contextual view of morality grounded in social relationships and human connectedness. Practically, this study recommends a moral education model that integrates rationality and empathy as the foundation for developing women’s character. Such an approach is essential to foster a generation capable of discerning right from wrong through logic while also possessing deep social awareness and emotional responsibility.